2021
DOI: 10.3389/fcimb.2021.768830
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioimpedance-Based Detection of Miltefosine Susceptibility Among Clinical Leishmania donovani Isolates of the Indian Subcontinent Exhibiting Resistance to Multiple Drugs

Abstract: The extent of susceptibility towards miltefosine (Mil), amphotericin B (AmpB), and paromomycin (Paro) was measured among 19 clinical isolates of Leishmania donovani (LD). Thirteen of these clinical isolates were reported to exhibit low susceptibility towards sodium stibogluconate (SSG-R), while six of them were highly susceptible (SSG-S). The degree of clearance of amastigotes (EC50) for these predefined SSG-R- and SSG-S-infected macrophages was determined against Mil, AmpB, and Paro. Two out of the 13 SSG-R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Next, to propound C17 as a new drug candidate against drug-resistant leishmaniasis, we tested its efficacy toward the LdTop1 from the antimony-resistant field isolate of L. donovani , BHU575 (less susceptible to SSG, amphotericin B, and miltefosine), obtained from severely VL affected belt of India. , First, we confirmed the similar levels of endogenous LdTop1 activity from the two strains of L donovani AG83 (wild type) and BHU575 (antimony-resistant) in the plasmid DNA relaxation assays (Figure S3A). Figure A shows that indeed C17 inhibited the relaxation activity of LdTop1 from Leishmania BHU575 whole cell extracts in a dose-dependent manner (Figure A, lanes 4–8), with an IC 50 of 8.75 μM (Figure B) which was comparable with wild type parasites (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to propound C17 as a new drug candidate against drug-resistant leishmaniasis, we tested its efficacy toward the LdTop1 from the antimony-resistant field isolate of L. donovani , BHU575 (less susceptible to SSG, amphotericin B, and miltefosine), obtained from severely VL affected belt of India. , First, we confirmed the similar levels of endogenous LdTop1 activity from the two strains of L donovani AG83 (wild type) and BHU575 (antimony-resistant) in the plasmid DNA relaxation assays (Figure S3A). Figure A shows that indeed C17 inhibited the relaxation activity of LdTop1 from Leishmania BHU575 whole cell extracts in a dose-dependent manner (Figure A, lanes 4–8), with an IC 50 of 8.75 μM (Figure B) which was comparable with wild type parasites (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The structure−activity relationships (SAR) of the twenty compounds resulting from the parental structure of the PIQ core suggested that compound C17 is the most potent LdTop1 inhibitor both in the in vitro and ex vivo DNA relaxations assays (Table 2). C17 inhibits the growth of both the antimony-resistant field isolate of Leishmania (BHU575) which is also known to be less susceptible toward the clinically used antileishmanials like sodium stibo-gluconate (SSG), miltefosine, paromomycin, and amphotericin B, 34 as well as the wild-type drug-responsive strain (Ag83) by targeting LdTop1. C17 did not inhibit the activity of human monomeric Top1 which further exalts its promise as a selective antileishmanial drug candidate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Knowledge of molecular changes associated with drug resistance and TF could help to increase the efficiency of new therapeutic strategies to be used in patients with leishmaniasis and TF. However, these studies have been undertaken principally in promastigote forms of Leishmania lines that are experimentally resistant to the common drugs, with very few studies including the use of clinical drug-resistant isolates and/or clinical isolates from patients with leishmaniasis and TF [ 19 , 20 , 21 ]. Molecular approaches to characterize the mechanisms of drug resistance or TF in these Leishmania lines include microarray studies [ 22 ], proteomic analysis [ 23 ], and, more recently, RNA-seq [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%